WHAT CAN WE LEARN FROM STUDENTS’ WRITTEN REFLECTIONS IN AN INTERCULTURAL COMMUNICATION THEORETICAL COURSE? - Thi Hoang Mai, Vu (VNU Journal of Foreign Studies, 2021)
The implementation of intercultural communication (IC) courses has been excitedly scrutinized particularly in multicultural education and training environments. However, little has been talked about such courses as a compulsory theoretical subject at tertiary institutions, especially where communicating across cultures is not a mandatory daily practice. Inspired by the researched merits of reflective thinking, this paper investigates what a lecturer of such a course can learn from her students' assigned written reflections. The analysis, both quantitative and qualitative, of the reflections of eight classes of third year students at a language education university in Hanoi throughout an IC theoretical course has revealed informative implications with respect to: (1) the students' interest and critical thinking in particular issues and/or frameworks in IC; (2) the students' self-regulation in studying such a theoretical subject; (3) the students' reflection levels and their conceptualization of the knowledge and their own learning. This analysis also attempts to discover the effectiveness of reflective writing in an IC theoretical course at the investigated institution, thereby proposing some recommendations to the reflection pedagogy currently employed at the university.